Randomized controlled clinical study evaluating the efficacy and safety of intratumoral treatment of canine mast cell tumors with tigilanol tiglate (EBC‐46). (16th June 2020) - De Ridder, Thomas R.; Campbell, Justine E.; Burke‐Schwarz, Cheryl; Clegg, David; Elliot, Emily L.; Geller, Samuel; Kozak, Wendy; Pittenger, Stephen T.; Pruitt, Jennifer B.; Riehl, Jocelyn; White, Julie; Wiest, Melissa L.; et al.
Abstract: Objective: To evaluate the efficacy and safety of tigilanol tiglate (TT) for local intratumoral treatment of mast cell tumors (MCTs) in dogs. Methods: A randomized controlled clinical study in 2 phases involving 123 dogs with cytologically diagnosed MCT. Phase 1 compared 81 TT‐treated dogs with 42 control dogs; phase 2 allowed TT treatment of control dogs and retreatment of dogs that failed to achieve tumor resolution after TT treatment in phase 1. Tigilanol tiglate (1 mg/mL) was injected intratumorally with dose based on tumor volume. Concomitant medications were used to minimize potential for MCT degranulation. Modified response evaluation criteria in solid tumors were used to evaluate treatment response at 28 and 84 days. Adverse events and quality of life were also assessed. Results: A single TT treatment resulted in 75% complete response (CR) (95% confidence interval [CI] = 61‐86) by 28 days, with no recurrence in 93% (95% CI = 82‐97) of dogs by 84 days. Eight TT‐treated dogs that did not achieve CR in phase 1 achieved CR after retreatment, increasing the overall CR to 88% (95% CI = 77‐93). Control dogs had 5% CR (95% CI = 1‐17) at 28 days. Wound formation after tumor slough and wound size relative to tumor volume were strongly associated with efficacy. Adverse events typically were low grade, transient, and directly associated with TT's mode of action. Conclusions: Tigilanol tiglate is efficacious and well tolerated, providing a new option for the local treatment of MCTs in dogs.